Pengaruh Keseimbangan Kehidupan Kerja dan Kompensasi terhadap Kepuasan Kerja Karyawan PT. Indomarco Bandung - Garibaldi, Ganjar (Banking & Management Review, 2019)
In this study the research was a problem related to the Balance of Work Life and Compensation in the company PT. Indomarco Bandung which can affect Employee Job Satisfaction. The purpose of this study is (1) To determine the effect of Work Life Balance on Employee Job Satisfaction at PT. Indomarco Bandung, (2) To determine the effect of work life balance on employee job satisfaction at PT. Indomarco Bandung, (3) To find out work discipline and work life balance and its effect on job satisfaction of employees of PT. Indomarco Bandung. The object of this research is all employees at PT. Indomarco Bandung and sampling techniques by applying Slovin formula. This study uses a questionnaire as a data collection tool. The test used to test the research instrument in the form of validity test and reliability test. Data analysis used multiple linear regression analysis, correlation coefficient, and coefficient of determination. The analysis shows that there is an influence and significant between Work Life Balance variable (X1) with Job Satisfaction variable (Y), There is influence and significant between Compensation variable (X2) and Employee Performance variable (Y). Work Life Balance and compensation simultaneously give an effect on the work satisfaction variable of 68.2%. Keywords: Work Life Balance, Compensation, Employee Job Satisfaction